4(2c-1)-3=6c+3

Simple and best practice solution for 4(2c-1)-3=6c+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2c-1)-3=6c+3 equation:


Simplifying
4(2c + -1) + -3 = 6c + 3

Reorder the terms:
4(-1 + 2c) + -3 = 6c + 3
(-1 * 4 + 2c * 4) + -3 = 6c + 3
(-4 + 8c) + -3 = 6c + 3

Reorder the terms:
-4 + -3 + 8c = 6c + 3

Combine like terms: -4 + -3 = -7
-7 + 8c = 6c + 3

Reorder the terms:
-7 + 8c = 3 + 6c

Solving
-7 + 8c = 3 + 6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6c' to each side of the equation.
-7 + 8c + -6c = 3 + 6c + -6c

Combine like terms: 8c + -6c = 2c
-7 + 2c = 3 + 6c + -6c

Combine like terms: 6c + -6c = 0
-7 + 2c = 3 + 0
-7 + 2c = 3

Add '7' to each side of the equation.
-7 + 7 + 2c = 3 + 7

Combine like terms: -7 + 7 = 0
0 + 2c = 3 + 7
2c = 3 + 7

Combine like terms: 3 + 7 = 10
2c = 10

Divide each side by '2'.
c = 5

Simplifying
c = 5

See similar equations:

| -2x+y-z=0 | | 6h-3h-5h-h-2h+2=11 | | 10y^2+49y-104=0 | | -0.75p+(-2)=0.25p | | 10b+-11b-5b+5b+6=16 | | 1x+14=-5 | | 20p-15p-5p+p+3p-3=5 | | 18g-12g-5g-1=5 | | 10h-7h=-9 | | -18v-(-17v+6v)-(-18)=-12 | | 20v-16v-(-v-9v)=20 | | 8t+2t-9t+1=8 | | 32-32x=(6x+4)(x-1) | | -6w+4(w-2)=-14 | | c+5c-5c=14 | | -2w+-w+-8=13 | | 11r+-20r+11r=-8 | | 20w+2w+4w-25w=12 | | 6x+12y=-12 | | 14b+(-4b+3b-19b)=12 | | -13z-(-15z)-(19z)=17 | | 14c+3-(16+c)=12 | | 2/7-4= | | 2s-s=19 | | 9m-27=0 | | 4f-6=10+2f | | 25x+2y+74=0 | | 7x+111=55+6x+58 | | 7x/4=22-c | | 3p-9=3 | | 10*2+y=217 | | 10x+207=217 |

Equations solver categories